Optimizing Outcomes for Liver and Pancreas Surgery (Springer International Publishing, 2018)
This book is designed to present a practical and evidence-based approach to liver and pancreas surgery that will provide both experienced and novice surgeons as well as surgical trainees a resource for optimizing their outcomes. The entire perioperative spectrum of care is addressed in chapters written by an international panel of experts in the field. Initial sections discuss preoperative assessment and intervention, fluid management, and perioperative pain control. Subsequent chapters focus on the specific aspects of operative approach and technique, including minimally invasive surgery, fluid management, parenchymal transection, and use of drains, tubes and stents. The text concludes with chapters on perioperative pain control, management of complications as well as the role of enhanced recovery pathways. A brief review of the existing literature addressing the particular topic follows in each section. Extensive illustrations, figures, and tables provide reinforcement to the educational content. Optimizing Outcomes for Liver and Pancreas Surgery will provide readers an easy to reference guide with easily accessible text and visual aidstent. Optimizing Outcomes for Liver and Pancreas Surgery will provide readers an easy to reference guide with easily accessible text and visual aids.